2015
DOI: 10.1177/1541931215591115
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pulse Oximetry Sonifications for Eyes Free Monitoring

Abstract: Pulse oximeters monitor a patient’s heart rate and oxygen saturation (SpO2) via visual and auditory displays. Heart rate is represented by the beep rate and SpO2 by beep pitch. However, the auditory display alone does not always accurately inform clinicians of the patient’s actual SpO2 level. Moreover, neonates have special oxygen needs that mean current pulse oximetry sounds are inadequate. In three studies we tested potentially improved pulse oximetry sounds for monitoring critically ill neonates. The contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 2 publications
1
8
2
Order By: Relevance
“…Power analysis was conducted before the experiment using G*Power (Heinrich‐Heine Universitaet, Dusseldorf) . The power analysis was based on previous pilot research that found a significant advantage of 12 percentage points for SpO 2 range identification accuracy with enhanced sonification and an effect size of d = 0.72 . The power analysis assumed two‐tailed t‐tests for independent groups with a Bonferroni corrected p value of p = 0.025 for two tests (primary outcome measures of range identification accuracy and target transition detection accuracy) and power of 0.80.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Power analysis was conducted before the experiment using G*Power (Heinrich‐Heine Universitaet, Dusseldorf) . The power analysis was based on previous pilot research that found a significant advantage of 12 percentage points for SpO 2 range identification accuracy with enhanced sonification and an effect size of d = 0.72 . The power analysis assumed two‐tailed t‐tests for independent groups with a Bonferroni corrected p value of p = 0.025 for two tests (primary outcome measures of range identification accuracy and target transition detection accuracy) and power of 0.80.…”
Section: Methodsmentioning
confidence: 99%
“…The sonification underlying both the control and enhanced conditions mapped linear increments of SpO 2 to logarithmic increments of sound frequency in Hz. For both conditions, each 1% increase in oxygen saturation level was mapped to a 2.62% increase in Hz . Pitch ranged from 525 Hz at 80% SpO 2 (we only tested discrimination in the 80–100% range) to 881 Hz at 100% SpO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As tremolo frequency increases, in cycles per tone or per second (Hz), the vibrating becomes more rapid. In a subsequent pilot study with a betweensubjects design, Hinckfuss et al (2015; Experiment 3) added three cycles of tremolo to tones in the low and high SpO2 ranges, and five cycles of tremolo to tones in the very low and very high SpO2 ranges (see Table 1 for ranges). A third dependent variable was also introduced: participants' accuracy at detecting when SpO2 first exited or entered its target range, as this moment is clinical important.…”
Section: Recent Enhancements Of Pulse Oximetry Sonification For Neonatesmentioning
confidence: 99%
“…Accordingly, we seek an improvement of at least 15 percentage points for the tremolo sonification over the log-linear sonification, and will define 15 percentage points as the minimum improvement expected in all comparisons. Second, the effect of the beacon on direction identification is tested again to determine whether or not the confusions experienced by some participants in Hinckfuss et al (2016; Experiment 2) and Hinckfuss et al (2015;Experiment 3) are repeatable, and a cause for concern.…”
Section: Recent Enhancements Of Pulse Oximetry Sonification For Neonatesmentioning
confidence: 99%